Sodium-glucose cotransporter 2 Inhibitors and COVID-19 outcomes in type 2 diabetes patients: A population-based cohort study - Cerina Dubois; Jasjeet K Minhas-Sandhu; Wajd Alkabbani; Jason R.B. Dyck; Dean T. Eurich (Diabetes Epidemiology and Management)
Introduction: Sodium-glucose cotransporter 2 (SGLT2) inhibitors (SGLT-2i) have been suggested to be beneficial in the management of Coronavirus disease 2019 (COVID-19); however, animal and clinical data have been inconsistent. The objective of this study was to assess the risk of SARS-CoV-2 infection and poor COVID-19-related outcomes associated with SGLT-2i use in patients with type 2 diabetes. Methods: This is a comparative population-based retrospective cohort study on new users of SGLT-2i or dipeptidyl peptidase-4 (DPP-4) inhibitors (DPP-4i) from January 1, 2012 to March 31, 2021 in Alberta, Canada. We assessed: 1) presence of a positive COVID-19 test (or seropositivity for SARS-CoV-2); 2) an all-cause event around positive COVID-19 test (hospital admission, emergency department visit, death); and 3) a COVID-19-specific-event(hospital admission, emergency department visit, death) around positive COVID-19 test. We estimated the hazard ratio (HR) and 95% Confidence interval (CI) using a conditional Cox proportional hazard regression after 1:1 high-dimensional propensity score (hdPS) matching. Results: There were 37,079 SGLT-2i and 39,053 DPP-4i users (30,433 matched pairs). After adjustment, compared to DPP-4i, SGLT-2i use was minimally associated with a positive COVID-19 test [HR: 1.23; 95% CI: 1.02–1.49]. Results were statistically significant across secondary cohort comparators for the risk of a COVID-19-positive test. SGLT-2i was also associated with a higher risk in a COVID-19-specific event [HR: 1.66; 95% CI: 1.12–2.45] compared to DPP-4i. Conclusion: SGLT-2i may be associated with a modest increase in positive COVID-19 tests across all compactors and COVID-19-specific events compared to DPP-4i among adults with type 2 diabetes. However, the clinical impact of this finding is uncertain. There is a need for further prospective studies to assess the relationship between SGLT-2i use and COVID-19-related outcomes in patients with type 2 diabetes.